Toronto. - Alberta College of Art Gallery, Calgary (Calgary : Alberta College of Art Gallery, 1980)
Astman, Barbara ; Bolley, Andrea ; Bowers, Robert ; Calzetta, Tony ; Craven, David ; Evans, Ric ; Frenkel, Vera ; Gomes, Mark ; Harding, Noel ; Leshyck, TOnie ; McEwen, John ; McNealy, Robert ; Schelle, Susan ; Steele, Lisa
The exhibtion, TORONTO has been diveded into two parts presented at Alberta College of Art Gallery, Calgary, September 11 - October 4, 1980 and October 9 - November 8, 1980
boek